Self-nanoemulsifying drug delivery systems (SNEDDS) for oral delivery of Garcinia kola seeds ethanolic extract: formulation and in vivo antimalarial activity. - Grady K. Mukubwa; Christian I. Nkanga; Aristote B. Buya; Jérémie K. Mbinze; Rui W.M. Krause; Patrick B. Memvanga (GarVal Editorial Ltda., 2020)
Context: Garcinia kola seeds are widely used in Congolese traditional medicine to treat uncomplicated malaria. While the ethanolic extract of these seeds (GK) is reputed for oral antimalarial activity, some of its constituents have shown poor water solubility, which might compromise further phytopharmaceutical developments. Aims: To develop a self-nanoemulsifying drug delivery system (SNEDDS) for oral delivery of GK, since SNEDDS are promising vehicles for enhancing drug product solubility. Methods: GK was loaded into liquid SNEDDS (solution and suspension) and solid SNEDDS (S-SNEDDS), and the resultant formulations were characterized using dynamic light scattering and electron microscopy. The antimalarial activity of SNEDDS (200 mg/kg × 4 days, oral) was evaluated in Plasmodium berghei-infected mice using a conventional four-day suppressive test. Results: The characterization of SNEDDS formulations revealed the presence of nanosized structures of spherical morphology and negative surface charge. Data from in vivo study showed reduced parasite growth by 77.9, 73.8 and 74.2% for GK-SNEDDS solution, GK-SNEDDS suspension and GK-S-SNEDDS, respectively. The activity of GK-SNEDDS was found to be greater than that of a licensed GK-based syrup (N'sansiphos®) used at the same dose (p<0.05). Conclusions: These findings demonstrate the potential of SNEDDS formulations as a promising alternative for enhancing the antimalarial efficacy of GK following oral administration. The SNEDDS technology holds the promise of improving the oral delivery of herbal-based products for malaria therapy.